Odpowiedź :
Odpowiedź:
(4+5x)(-2+y)= -8+4y-10x+5xy
(6x-3y)(3x-y)=18[tex]x^{2}[/tex]-6xy-9xy-3[tex]y^{2}[/tex]=18[tex]x^{2}[/tex]-15y-3[tex]y^{2}[/tex]
(-6a-b)(a+b)=-6[tex]a^{2}[/tex]-6ab-ab-[tex]b^{2}[/tex]=6[tex]a^{2}[/tex]-7ab--[tex]b^{2}[/tex]
(4x-y)(4x+y)=16[tex]x^{2}[/tex]-[tex]y^{2}[/tex]
(3a-2b)(-b+2a)=-3ab+6[tex]a^{2}[/tex]-2[tex]b^{2}[/tex]-4ab
Szczegółowe wyjaśnienie:
Mam nadzieję, że pomogłem. Liczę na naj :)
Odpowiedź:
(4 + 5x)(-2 + y) = -8 + 4y -10x + 5xy
(6x-3y)(3x-y)= 18x² - 6xy - 9xy + 3y² = 18x² - 15xy + 3y²
(-6a-b)(a+b)= -6a² - 6ab - ab - b² = -6a² - 7ab - b²
(4x-y)(4x+y) = 16x² + 4xy - 4xy - y² = 16x² - y²
(3a-2b)(-b+2a) = -3ab + 6a² + 2b² - 4ab = 6a² - 7ab + 2b²
Szczegółowe wyjaśnienie: